Measuring pH in insulin secretory granules by phasor-based fluorescence lifetime imaging of a genetically encoded sensor - Valentina De Lorenzi; Samuele Ghignoli; Mario Bernardi; Giulia Matteoli; Gianmarco Ferri; Barbara Storti; Ranieri Bizzarri; Francesco Cardarelli (Communications Biology)
Abstract It is widely accepted that the pH of insulin granules is acidic, and that its active regulation during granule maturation plays a role in the process of insulin secretion by β-cells. Yet, a calibrated measurement of the absolute granule pH with organelle specificity is still lacking. To tackle this issue, we use the genetically encoded E1GFP pH reporter inserted into the C-peptide of proinsulin and expressed in Insulinoma 1E cells. Following verification of correct targeting of the E1GFP reporter in the insulin granules, phasor-based Fluorescence Lifetime Imaging Microscopy (FLIM) is applied to obtain a calibrated and probe-concentration-independent measurement of insulin-granule pH. Our results confirm the acidic nature of insulin granules under maintenance cell culture conditions, with an average luminal pH of ~5.8, and show that acidity is actively maintained, as evidenced by its near-neutralization upon treatment with the vacuolar H+-ATPase inhibitor concanamycin. Additionally, by exploiting the intrinsic spatial resolution of FLIM, we highlight that granules which are proximal to the plasma membrane are slightly more acidic than those which are distal, a difference preserved even during the early phase of glucose-induced insulin secretion. This study lays the foundations for future investigations of granule pH in physiology and disease.